The Impact of the REACT Strategy on the Academic Achievement and Problem-Solving Skills of the Twelfth-Grade Students in Biology in the United Arab Emirates - SAID, THOURAYA MOHAMED (2024)
This study aimed to test the effectiveness of the REACT Strategy on academic achievement and problem-solving skills of twelfth-grade female biology students in the United Arab Emirates. Participants consisted of (60) female students in the twelfth grade at the Applied Technology High School (ATS) during the third semester of the scholastic year (2023-2024). The sample students were divided into two groups of (30) students: An experimental and a control group. The research instruments included a biology pre- and post-achievement test and a qualitative questionnaire to test the students’ perceptions and experiences of using the REACT strategy in the biology classroom. The validity of the research instruments was assured by the judging faculty, and the consistency was assured through testing and re-testing of an exploratory group of (30) female students. After ensuring the two research groups' homogeneity regarding age, readiness to learn biology, achievement, and problem-solving skills in biology, the two research groups went through the same experience. Still, one was exposed to ADEK’s biology curriculum, whereas the other group went through the RACT strategy for teaching and learning. The research findings revealed statistically significant differences between the two research groups on the biology achievement test scores in its post-application in favor of the female students of the experimental group. This shows the significant effect of the REACT strategy in improving academic achievement and problem-solving skills in biology before applying the strategy. Moreover, findings from the qualitative analysis indicated insights into students’ perceptions and experiences with the REACT approach, highlighting its role in fostering a supportive and interactive learning environment that reflects deep learning and critical thinking. Finally, this research provides valuable input for educators, policymakers, curriculum developers, and researchers seeking to optimize teaching and learning experiences in STEM disciplines. By adopting evidence-based strategies and fostering a culture of collaboration and inquiry, stakeholders can create optimal conditions for student success and promote equitable access to high-quality STEM education for all learners.